Effects of depression on medication adherence in HIV/AIDS patients: Korea HIV/AIDS cohort study - Kyung Sun Oh; Jin Soo Lee; Hyeon Chang Kim; Hye-Young Kang; Ju-Yeun Lee; Euna Han (Elsevier, 2023)
Background: The number of people with HIV/AIDS has consistently increased in Korea since the first case of HIV/AIDS infection was reported in 1985. The depressive symptoms of patients with HIV/AIDS may lead to medication non-adherence. This study sought to investigate the cross-sectional and longitudinal association between depression and antiretroviral treatment adherence in the Korean HIV/AIDS population. Methods: We included participants of the Korea HIV/AIDS cohort study between 2009 and 2017. All information was collected at the enrollment and every annual visit, including sociodemographic characteristics, health-related behaviors, HIV/AIDS infection-related factors, depression score, and frequency of skipped medication. We performed a cross-sectional analysis of 601 participants registered between 2009 and 2017. Longitudinal data were evaluated by panel regression analysis in 515 patients who registered from 2009 to 2013. Results: In cross-sectional analysis, the HIV/AIDS patients with depressive symptoms were more likely to be non-adherent (adjusted OR = 0.52, 95 % CI 0.34, 0.79, p = 0.002). Medication adherence was significantly associated with a health-related lifestyle; the adjusted odds ratio of the non-smoking and non-drinking group was 1.75 (95 % CI 1.05, 2.90, p = 0.031). The longitudinal panel regression model revealed a significant negative impact of depression on medication adherence (adjusted OR = 0.50, 95 % CI 0.30, 0.84, p = 0.009). Non-smoking and non-drinking participants were 2.31 times more likely to adhere to antiretroviral treatment (95 % CI 1.29, 4.15, p = 0.005). Conclusions: Our finding of depression and lifestyle modifications being significant contributors underscore the importance of proactive interventions to optimize the treatment outcomes of PLWH.